2016
DOI: 10.1007/s00038-016-0904-y
|View full text |Cite
|
Sign up to set email alerts
|

(Non-)utilization of pre-hospital emergency care by migrants and non-migrants in Germany

Abstract: To prevent over-, under-, and lack of supply, it is necessary to transfer knowledge about the functioning of the medical emergency services, including first aid knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
7
0
4
Order By: Relevance
“…The small number of studies ( n = 3) that examined emergency care utilization do not enable a definitive conclusion. One current publication showed higher utilization [ 40 ] among PMB while two others found no differences [ 26 , 41 ]. Also, the four studies regarding the utilization of rehabilitation (out- and inpatient) provide insufficient evidence [ 26 , 42 44 ], albeit the trend suggests a lower participation among PMB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The small number of studies ( n = 3) that examined emergency care utilization do not enable a definitive conclusion. One current publication showed higher utilization [ 40 ] among PMB while two others found no differences [ 26 , 41 ]. Also, the four studies regarding the utilization of rehabilitation (out- and inpatient) provide insufficient evidence [ 26 , 42 44 ], albeit the trend suggests a lower participation among PMB.…”
Section: Resultsmentioning
confidence: 99%
“… Inpatient care 10 [ 17 , 18 , 23 , 25 , 26 , 29 , 30 , 37 39 ] O ▪ Inconsistent results, differences in terms of type of disease. Emergency care 3 [ 26 , 40 , 41 ] O ▪ Inconsistent results: Higher probability of utilization among migrant adults, but no difference among children and adolescents. Rehabilitation 4 [ 26 , 42 44 ] ▪ Results tend to lower usage among migrants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the background of the current organisation of urgent and emergency care services in Germany, the present study introduces the individual predisposing factors sex, age, education, migration background and having children into the analyses of utilisation. Predisposing factors as lower education and a migration background are often associated with more frequent or inadequate prehospital and hospital emergency care utilisation in Germany and further European countries,7 23–26 although some current findings for Germany did not confirm these inequalities 27–29. Moreover, higher age predicts increased ED use while sex does not seem to play a significant role 7 24 27 28.…”
Section: Introductionmentioning
confidence: 68%
“… 53 In addition, children in seventh and eighth grade were more likely to have cold or diarrhoea instead of some serious illnesses, which may often be managed through self-medication. 54–56 However, parents in the low-acculturation group were more likely to have limited knowledge to implement successful self-medication, thereby choosing to use outpatient service after their children got ill. 57 Although parents in the low-acculturation group and poor economic status had a higher rate of outpatient service utilisation, the health facilities they chose were more likely to be society-run clinics (26.8%, the so-called private clinics), which generally have poorer service quality and lower medical expenditure without a licence, 58 instead of governmental health facilities, compared with other groups. This proportion was even higher than that among the IM workers in one study, which found that 20% IM workers selected the society-run clinic to see a doctor.…”
Section: Discussionmentioning
confidence: 99%